The Role of Small RNAs During the Interaction Between Sclerotinia Sclerotiorum and Brassica Napus - Regmi, Roshan (Curtin University, 2022)
Canola (Brassica napus) is an important oilseed crop and Sclerotinia stem rot (SSR) caused by Sclerotinia sclerotiorum, causes significant economic losses in canola. This thesis investigates the role of small RNAs (sRNAs), which are short non-coding RNAs that regulate various biological processes in eukaryotes and investigates their role in the B. napus – S. sclerotiorum interaction.